2003
DOI: 10.1007/s00122-003-1230-3
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-based marker system monitoring CMS-(S), CMS-(T) and (N)-cytoplasm in the onion (Allium cepa L.)

Abstract: The chimerical mitochondrial CMS(1)-specific sequence in chives ( Allium schoenoprasum) was used to develop a PCR-marker that distinguishes both male-sterility inducing cytoplasms, CMS-(S) and CMS-(T), from the normal cytoplasm in onion ( Allium cepa). In combination with a previously described marker for CMS-(S), which anchors in the upstream region of the mitochondrial gene cob, all of the three known cytoplasms in the onion are distinguishable. The PCR-marker system was tested in 361 onion plants, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 23 publications
0
43
0
2
Order By: Relevance
“…This accession was obtained from a local market in Bursa, Turkey, and could be a hybrid onion cultivar with sterile cytoplasm. Indeed, PCR analyses with 2 different PCR-based markers developed by Sato (1998) and Engelke et al (2003) demonstrated that this A. cepa accession had "S" cytoplasm (data not presented). In addition, these markers were also amplified within the genome of A. roylei and the sizes of the PCR-amplified DNA fragment were similar to that of "S" cytoplasm in A. cepa.…”
Section: Discussionmentioning
confidence: 98%
“…This accession was obtained from a local market in Bursa, Turkey, and could be a hybrid onion cultivar with sterile cytoplasm. Indeed, PCR analyses with 2 different PCR-based markers developed by Sato (1998) and Engelke et al (2003) demonstrated that this A. cepa accession had "S" cytoplasm (data not presented). In addition, these markers were also amplified within the genome of A. roylei and the sizes of the PCR-amplified DNA fragment were similar to that of "S" cytoplasm in A. cepa.…”
Section: Discussionmentioning
confidence: 98%
“…Since the fertility restoring gene for Zhangqiu-and Guangzhou-derived CMS has not been discovered in this study, we have compared the nucleotide sequences of three mitochondrial genes, cob, coxI and V7 region of srRNA among 'Zhangqiu', 'Guangzhou' and four F 1 commercial cultivars, 'Natsuougi-2', 'Fuyuougi-2', 'Ryuushou' and 'White Tower'. The primer sequences and PCR conditions for amplification of these genes were according to the reports of Engelke et al (2003) for cob, Kim et al (2009) for coxI and Buiteveld et al (1998) for V7 region of srRNA. In the three regions, sequence polymorphism was not detected among the six materials (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The orfA501 marker (Engelke et al, 2003) successfully amplified a 473bp chimerical orfA501 fragment associated with S or T cytoplasm (another system of male sterility not commonly used in breeding) in all onion samples designated as S (Figure 1; orfA501; line 1: all samples except 5 and 7; line 2: all samples; lines 3 and 4: only samples 6 and 7, respectively). Sample 8 of line 1 did not initially show a fragment with marker orfA501 (Figure 1, cytoplasmic genotype S * ), and was attributed to omitted gDNA template in the PCR.…”
Section: Preliminary Testing Of Pcr Molecular Markers For Determinatimentioning
confidence: 99%
“…A 180bp fragment is amplified from the N-cytoplasm with a N-specific primer and the same common reverse primer. The use of the three primers (S-, N-specific and common reverse primer) together in the same PCR is recommended by Engelke et al (2003) so that sub-stoichiometric amounts of the 414bp S-fragment is not amplified in N-cytoplasm. Both fragments are amplified in S-cytoplasm.…”
Section: Preliminary Testing Of Pcr Molecular Markers For Determinatimentioning
confidence: 99%
See 1 more Smart Citation